2021
DOI: 10.7189/jogh.11.04051
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of school feeding on educational and health outcomes of school-age children and adolescents in low- and middle-income countries: A systematic review and meta-analysis

Abstract: Background School feeding programs are ubiquitous in low- and middle-income countries (LMICs) and may have critical implications for the health and education of school-age children and adolescents. This systematic review aimed to assess the impacts of school feeding on educational and health outcomes of children and adolescents in LMICs. Methods Interventional studies on the effects of school feeding on nutritional and health outcomes of children and adolescents receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 73 publications
(133 reference statements)
0
20
1
Order By: Relevance
“…Food insecurity was prevalent among adolescent students in this global sample, with 25%–30% of students, depending on age group and sex, reporting going hungry because there was not enough food at some point in the last 30 d. Hunger is an experience associated with very low food security and is relatively infrequent compared with food-related worries or cutbacks in food quality ( 31 ), so the actual prevalence of less severe food insecurity is likely higher than was assessed with the 1 question available in the GSHS. This finding highlights the importance of monitoring and intervention to promote food security, including among students who are generally at lower risk of food insecurity in part owing to the food they receive while in school ( 32 ).…”
Section: Discussionmentioning
confidence: 94%
“…Food insecurity was prevalent among adolescent students in this global sample, with 25%–30% of students, depending on age group and sex, reporting going hungry because there was not enough food at some point in the last 30 d. Hunger is an experience associated with very low food security and is relatively infrequent compared with food-related worries or cutbacks in food quality ( 31 ), so the actual prevalence of less severe food insecurity is likely higher than was assessed with the 1 question available in the GSHS. This finding highlights the importance of monitoring and intervention to promote food security, including among students who are generally at lower risk of food insecurity in part owing to the food they receive while in school ( 32 ).…”
Section: Discussionmentioning
confidence: 94%
“…A recent systematic review of randomised control trials in LMICs found that school feeding was positively associated with height and weight; although, they did not find significant changes in height-for-age, weight-for-age, or body mass index-for-age. This indicates a need for further long-term studies to fully measure anthropometric changes [93].…”
Section: Nutrition Can Be Prioritisedmentioning
confidence: 99%
“…At the intersection of education and SDG5 (Gender Equality), school feeding has been linked to improved school attendance and performance, especially for girls [93,98,99]. Food procurement can also economically empower female food producers, which is why the FAO recommends giving women producers preferential access to public food procurement markets [88,100].…”
Section: Links To the Sustainable Development Agendamentioning
confidence: 99%
“…9 In addition, several studies in low-and middle-income countries have shown that school meal programmes have positive effects in correcting nutritional deficiencies and improving children's growth as measured by weight and height. 10 Including locally produced food in school meals could also provide structured institutional demand and a predictable market for smallholder farmers, benefitting child nutrition as well as food security more broadly. 11 However, we reiterate that current global inequalities resulting from the negative effects of climate change point to the urgent need to transform and adapt food systems from the global to the local level to ensure nutritious diets for children in all parts of the world.…”
mentioning
confidence: 99%
“…Such measures can contribute to positive health and nutrition outcomes for school aged children, for example, weekly iron supplementation for adolescents has been shown to reduce the risk of anaemia, and nutritional education through school gardens has improved school children’s nutritional agency 9. In addition, several studies in low- and middle-income countries have shown that school meal programmes have positive effects in correcting nutritional deficiencies and improving children’s growth as measured by weight and height 10. Including locally produced food in school meals could also provide structured institutional demand and a predictable market for smallholder farmers, benefitting child nutrition as well as food security more broadly 11.…”
mentioning
confidence: 99%